A quality assessment of clinical practice guidelines with recommendations for family involvement in the care of individuals diagnosed with schizophrenia, bipolar mood disorder, and major depressive disorder: Critical appraisal utilizing AGREE II - Dehbozorgi, Raziye; Fereidooni-Moghadam, Malek; Shahriari, Mohsen; Moghimi-Sarani, Ebrahim (Frontiers in Psychiatry, 2023)
Introduction Evidence suggests that family-center collaborative care is useful for individuals identified with chronic mental illness. Clinical practice guidelines offer specific recommendations primarily based on to be had studies and are beneficial in informing evidence-based practice and guiding destiny studies. Objective Identify current scientific practice guidelines including family-center collaborative care suggestions for individuals with Bipolar Mood Disorder, Schizophrenia, and Major Depressive Disorder and analyze the selection of guidelines for their methodological quality. Methods A systematic search was conducted on seven electronic databases (G-I-N), (NICE), (MOH), (SIGN), (WHO), (NIH) and (APA) and additional sources. Three referees independently reviewed articles and selected guidelines for inclusion criteria. Subsequently, 18 trained appraisers independently assessed all 15 guidelines using AGREE II. Results The mean scores for domains and overall quality were computed. For the overall assessment of the guidelines, 60% reached the quality threshold with domain scores of 60%. The overall average quality rating for these guidelines was 58/29%. Conclusion The applicability of the guidelines needs to be improved in order to improve their relevance and clinical utilization. As individuals with chronic mental illnesses progress through their disease course, families and health care providers play a crucial role in helping them. The analysis of research knowledge on effective rehabilitation techniques, including the involvement of families in treatment, can be enhanced by using well-developed and appropriate methods.